Market segmentation and supply‐chain predictability: evidence from China. (11th May 2019) - Li, Chenchen; Li, Rui; Diao, Xundi; Wu, Chongfeng
Abstract: We determine the industry‐level supply‐chain predictability in the Chinese stock market. Evidence is provided that a limited information model is gradually adaptive to the Chinese stock market in recent years, while several traditional measures of informed trading perform differently in the previous period. An innovative indicator of the mobile ratio volatility is also proposed here, which relates the increasing mobile trading behavior to this cross‐sectional predictability. Furthermore, we explain the asymmetry of customer and supplier momentum in this market.